Public Child Care and Mothers' Labor Supply - Evidence from Two Quasi-Experiments - Stefan Bauernschuster; Martin Schlotter (Center for Economic Studies and ifo Institute (CESifo), 2013)
Public child care is expected to assist families in reconciling work with family life. Yet, empirical evidence for the relevance of public child care to maternal employment is inconclusive. We exploit the introduction of a legal claim to a place in kindergarten in Germany, which was contingent on day-of-birth cut-off dates and resulted in a marked increase in kindergarten attendance of three-year olds in the following years. Instrumental variable and difference-indifferences estimations on two individual-level data sets yield large and positive effects of public child care on maternal employment. A set of placebo treatment tests corroborate the validity of our identification strategies.
Keywords: J22; J13; D04; 330; public child care; maternal employment